An unusual propagation pattern along the tricuspid annulus after cavo-tricuspid isthmus ablation: Insights into posterior transverse conduction revealed by an ultra-high-resolution 3-dimensional mapping system. Issue 3 (March 2019) - Kanda, Takashi; Masuda, Masaharu; Kurata, Naoya; Matsuda, Yasuhiro; Osamu, Iida; Asai, Mitsutoshi; Mano, Toshiaki
Abstract: Cavo-tricuspid isthmus (CTI) ablation is a cornerstone of atrial flutter ablation. The goal of CTI-dependent flutter ablation is achievement of bidirectional CTI block. Usually bidirectional CTI block is confirmed by atrial activation during septal and lateral atrial pacing or the use of differential pacing maneuvers. According to the pathological findings, the transmural muscle fibers connect the endo- and epicardium. An epicardial-endocardial breakthrough (EEB) sometimes interferes with the confirmation of bidirectional block. Recently, a new ultra-high-resolution 3-dimentional mapping systems (Rhythmia ®, Boston Scientific, Marlborough [Cambridge] MA, USA) that allows rapid ultra-high-resolution electroanatomical mapping was introduced. A 64-year-old man with a sustained atrial flutter (AFL) was referred to us. Catheter ablation was performed using an ultra-high-resolution 3-dimensional mapping system. Here, we report the case of a patient with an EEB visualized by ultra-high-resolution 3-dimensional mapping. <Learning objective: The crista terminalis are recognized as the anatomic structure responsible for line of conduction block at the posterior right atrial wall. This block line is mainly functional, and transverse conduction across the posterior wall can be observed. This is the first report to visualize the EEB and examine its influence on the conventional electrophysiological findings.>